Studying of stress-strain state of hip joint elements in case of aseptic femoral head necrosis in children (the second message) - Korolkov, Oleksandr; Katsalap, Yelyzaveta; Karpinsky, Mykhaylo; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to study the stress-strain state of the hip joint elements in cases of different localization of the destruction of the femoral head due to aseptic necrosis in children with lesions 50 and 75 % of its volume. Methods: on mathematical models of the hip joint, the stress-strain state was investigated in the case of femoral head defects of 50 and 75 % of its volume of various localization. The model consisted of components with the properties of cancellous and compact bone tissue, as well as with growth zones with the mechanical characteristics of cartilage. The models were loaded with a vertical distributed force of 270 N. Reproduced the action m. gluteus medius of 450 N and m. gluteus minimus force of 200 N. Results: when we increased the area of the femoral head defect up to 50 % at weight bearing on a limb the values of maximum stresses increased in all studied areas of the model compared to the normal state and the case of 25 % defect. At increased defect up to 75 % in the critical zone, the stress-strain state reached the number of 31.9 MPa, stress increased on its lateral edge in the cortical layer up to 25.6 MPa, and in the cancellous bone up to 9.1 MPa. Stress decreased on the medial edge of the defect to 5.0 MPa in the cortical layer and up to 0.8 MPa — in the cancellous bone. Near the middle part of the defect stress increased in the cortical layer to 4.8 MPa, and in the cancellous bone decreased to 0.8 MPa. Conclusions: in the models with a lesions size of 50 and 75 %, the most unfavorable is the location of the defect on the border of the upper edge of the acetabulum and the upper part of the femoral head, in the zone of its greatest load. If the volume of the femoral head goes up to 50 %, with the weight bearing on the limb the values of maximum stresses increase practically on all studied areas of the hip joint model. The size of the lesion of the femoral head up to 75 % leads to an increasing of magnitude of the stresses in the loaded areas and to a decreasing in other investigated areas.